Stillbirth due to unrecognized transposition of the great arteries - Raj Selvaraja, Ganesh; Syahir, Hazimin; Subramaniam, Kunasilan; Binti Ibrahim , Norliza (Journal of Indian Academy of Forensic Medicine, 2020)
Congenital cardiac anomalies attributed to 4.2% of all neonatal deaths globally, whereas transposition of the great arteries were 5-7%  of all congenital cardiac anomalies. The vascular system of the foetus starts to develop by day 17 of the embryonic life. This early  development of the vascular system provides the opportune window for disruption to the normal development. The anomalies can  range from being minor to fatal. Review of the medical literatures, stated a two – to threefold increase in malformation rates related to  infants of insulin dependent diabetic mothers. Fatal malformations in infants of diabetic mothers compared to infants of non-diabetic  mothers were 2.1% and 0.3% respectively. We discuss the importance of conducting an autopsy on stillbirths in determining the true  cause of death and keeping in mind the possibility of genetic anomalies, environmental factors, foeticide or non-accidental injuries  being a contributing factor. Here we report a case of a 23-year-old married; primigravida woman whom delivered a foetus at home.  This was an unregistered pregnancy. The woman was on insulin therapy for her underlying Type 1 Diabetes Mellitus. Post-mortem  examination determined the cause of death. The internal examination revealed transposition of the aorta and pulmonary artery. The  cause of death attributed to stillbirth due to transposition of the great arteries in infant of a diabetic mother.
Keywords: Autopsy; Stillbirth; Congenital Heart Anomaly; Transposition of Great Arteries